Dampak tingkat inflasi dan kualitas lingkungan terhadap pertumbuhan ekonomi di Indonesia - Claudia, Emilia Ruth; Fitrawaty, Fitrawaty; Nugrahadi, Eko Wahyu (Journal of Economics Research and Policy Studies, 2024)
This study aimed to analyze the impact of inflation rate and environmental quality on Indonesia's economic growth during 2019-2022. The research uses panel data regression methods with the Fixed Effect Model (FEM) approach to examine the influence of independent variables on the dependent variable. Secondary data were obtained from various official sources, including Statistics Indonesia (BPS) and the Ministry of Environment and Forestry. The results show that the inflation rate has a negative effect on economic growth, whereas high inflation reduces economic growth. Environmental quality positively affects economic growth, indicating that improvements in environmental quality can promote economic growth. Simultaneously, all independent variables, both inflation rate and environmental quality, significantly influence economic growth in Indonesia. This study concludes that controlling inflation and improving environmental quality are crucial in promoting sustainable economic growth in Indonesia.